Acute effects of different warm-up protocols with and without a weighted vest on jumping performance in athletic women - Thompsen, A. G.; Kackley, T.; Palumbo, M. A.; Faigenbaum, A. D. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this study was to examine the acute effects of 3 different warm-up protocols with and without a weighted vest on vertical jump (VJ) and long jump (LJ) performance in athletic women. Sixteen subjects (19.7 +/- 1.4 years, 67.0 +/- 10.7 kg, 165.7 +/- 11.4 cm) participated in 3 testing sessions in random order on 3 nonconsecutive days. Prior to the testing of the VJ and LJ, the subjects performed 1 of the following 10-minute warm-up protocols: (a) low- to moderate-intensity stationary cycling followed by 4 lower-body static stretches (SS) (3 x 20 seconds); (b) 12 moderate- to high-intensity dynamic exercises (DY); and (c) the same 12 dynamic exercises with a weighted vest (10% of body mass) worn for the last 4 exercises (DYV). Analysis of the data revealed that VJ performance was significantly greater (p < 0.05) following DYV (43.9 +/- 6.7 cm) and DY (43.6 +/- 6.5 cm) as compared to SS (41.7 +/- 6.0 cm). Long jump performance was significantly greater (p < 0.05) following DYV (186.8 +/- 19.5 cm) as compared to DY (182.2 +/- 19.1 cm), which in turn was significantly greater (p < 0.05) than performance following SS (177.2 +/- 18.8 cm). Warm-up protocols that include dynamic exercise may be a viable method of enhancing jumping performance in athletic women as compared to stationary cycling and static stretching. In addition, these data suggest that it may be desirable for athletic women to perform dynamic exercises with a weighted vest on some movements prior to the performance of the long jump.